ANALISIS KEKUATAN VELG CAST WHEEL SEPEDA MOTOR DENGAN PERANGKAT LUNAK BERBASIS METODE ELEMEN HINGGA - Irawan, Andi Husni; Majanasastra, R.Bagus Suryasa; Rahmanto, R. Hengki (Jurnal Ilmiah Teknik Mesin, 2016)
Cast wheel on a motor cycle is a structure from a tire that able to hold force from the weight of a vehicle and passengers. In this research is analyze effect of spoke quantity on a cast wheel rims of a motor cycle, stress and deformation that actually happen on cast wheel can be know by using the help of a mathematical software that using finite element method. Local motor cycle cast wheel rims industry is usually using trial and error when developing their products (Zuliantonil, 2007). Trial and error when developing a motor cycle cast wheel rims is a method that against with principal of sustainable product design. To make design and testing easy, mathematical software based by finite element method is used to analyze structure of cast wheel rims. In this research is achieved maximum stress that occur on cast wheel that using three rims is 2.1284e+7 N/m2 and the maximum deformation is 0.00020485 m, while maximum stress that occur on cast wheel that using five rims is 2.3171e+7 N/m2 and the maximum deformation 0.00013528 m. Three rims cast wheel is a design that can represent the best design with principal efficiency mass products productivity, because can cut material cost in a product without rule out the esthetics value and safety aspects for consumer.